Concepts of Load Handling Devices, Adjusted to Light Goods Vehicles of The Weight up to 3.5t - Drozdziel, Pawel; Wawer, Kamil; Madlenak, Radovan; Mussabekov, Murat Omarbekovich (Communications - Scientific letters of the University of Zilina, 2017)
The main aim of the article is to present three concepts of load handling devices, adjusted to light goods vehicles of the weight up to 3.5 t. The design issue commissioned by Poczta Polska - the Polish Post was analysed. On the basis of the analysis the design assumptions were taken to design a device. The construction and the method of operation of the design structures suggested by the author were discussed. All the concepts were compared with one another with the use of a SWOT analysis.